2013
DOI: 10.1016/j.toxicon.2013.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of membrane phospholipids, the cytosolic calcium influx and cell proliferation following treatment of B16-F10 cells with recombinant phospholipase-D from Loxosceles intermedia (brown spider) venom

Abstract: The mechanism through which brown spiders (Loxosceles genus) cause dermonecrosis, dysregulated inflammatory responses, hemolysis and platelet aggregation, which are effects reported following spider bites, is currently attributed to the presence of phospholipase-D in the venom. In the present investigation, through two-dimensional immunoblotting, we observed immunological cross-reactivity for at least 25 spots in crude Loxosceles intermedia venom, indicating high expression levels for different isoforms of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…In the case of ␤1A1 (SMase II) from L. laeta, SMase D activity has been observed but with a 3-fold higher K m value and a reported 2-fold lower reaction rate at saturating substrate concentrations compared with ␣III1 (SMase I) from the same species (26). References for structure and activity data are as follows: IsSMase (74); LiRecDT6 (11); LiRecDT7 (14); SMase I (8,18,27,35,59,64,75); Ll2 (8); LiRecDT4 (9); LgRec1 (76); Lr1/Lb1/Lb2 (8,25); L. arizonica ␣IB2bi (15,30); Lr2 (19,25); P1/P2 (77-79); LiRecDT1 (6,7,12,13,20,60); 3RLG (61); 3RLH (28); LiRecDT2 (7); LiRecDT5 (9); Lb3 (8,25); LiRecDT3 (7,10); and SMase II (26).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of ␤1A1 (SMase II) from L. laeta, SMase D activity has been observed but with a 3-fold higher K m value and a reported 2-fold lower reaction rate at saturating substrate concentrations compared with ␣III1 (SMase I) from the same species (26). References for structure and activity data are as follows: IsSMase (74); LiRecDT6 (11); LiRecDT7 (14); SMase I (8,18,27,35,59,64,75); Ll2 (8); LiRecDT4 (9); LgRec1 (76); Lr1/Lb1/Lb2 (8,25); L. arizonica ␣IB2bi (15,30); Lr2 (19,25); P1/P2 (77-79); LiRecDT1 (6,7,12,13,20,60); 3RLG (61); 3RLH (28); LiRecDT2 (7); LiRecDT5 (9); Lb3 (8,25); LiRecDT3 (7,10); and SMase II (26).…”
Section: Methodsmentioning
confidence: 99%
“…PLD toxins from Loxosceles bind to mammalian cell surfaces [9] and have enzymatic activity against common phospholipids in mammalian tissue, including lysophosphatidylcholine (LPC) and sphingomyelin (SM) [2], [4], [10]. The most common activity assay for these enzymes detects PLD activity by monitoring choline release from substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Because this cascade can be activated by interactions outside the cell, we speculate that the venom of L. similis may interact with receptors on the cell surface. Many studies have shown the binding of Loxosceles venom toxins upon the membrane of diverse cell types, showing direct induction of cytotoxicity and supporting the hypothesis of “planted antigens” to different components of cell structures (Chaim et al, 2006; Chaves-Moreira et al, 2009; Dias-Lopes et al, 2010; Wille et al, 2013). Further research should be done to investigate which venom compounds can activate the caspases cascade investigated.…”
Section: Discussionmentioning
confidence: 78%